Entity comparison in knowledge graphs - Petrova, A (2019)
Knowledge graphs (KGs) represent information in a simple, interlinked format and are used in a variety of applications. Besides the standard reasoning tasks such as query answering, there has been an increasing need for new types of analysis. One such fundamental analysis task is entity comparison, i.e., determining what two entities have in common and how they are different. The importance of such a task can be seen in various applications such as product comparisons, and explainable recommender systems. This thesis studies the problem of entity comparison over knowledge graphs and presents a novel framework that models comparisons via similarity and difference queries. It is the first declarative comparison framework for linked data that treats both similarities and differences as first-class citizens.